Temperature-dependent expression of virulence genes in fish-pathogenic bacteria - Guijarro, José A.; Cascales, Desirée; García-Torrico, Ana I.; García-Domínguez, Mario; Méndez, Jessica (Frontiers in Microbiology, 2015)
Virulence gene expression in pathogenic bacteria is modulated by environmental parameters. A key factor in this expression is temperature. Its effect on virulence gene expression in bacteria infecting warm-blooded hosts is well documented. Transcription of virulence genes in these bacteria is induced upon a shift from low environmental to a higher host temperature (37 ºC). Interestingly, host temperatures usually correspond to the optimum for growth of these pathogenic bacteria. On the contrary, in ectothermic hosts such as fish, molluscs and amphibians, infection processes generally occur at a temperature lower than that for the optimal growth of the bacteria. Therefore, regulation of virulence gene expression in response to temperature shift has to be modulated in a different way to that which is found in bacteria infecting warm-blooded hosts. The current understanding of virulence gene expression and its regulation in response to temperature in fish-pathogenic bacteria is limited, but constant extension of our knowledge base is essential to enable a rational approach to the problem of the bacterial fish diseases affecting the aquaculture industry. This is an interesting issue and progress needs to be made in order to diminish the economic losses caused by these diseases. The intention of this review is, for the first time, to compile the scattered results existing in the field in order to lay the groundwork for future research. This article is an overview of those relevant virulence genes that are expressed at temperatures lower than that for optimal bacterial growth in different fish-pathogenic bacteria as well as the principal mechanisms that could be involved in their regulation.